Indicator-based sustainability assessment of the smallholder beef cattle production system in South Africa. Issue 1 (2nd January 2017) - Marandure, Tawanda; Mapiye, Cletos; Makombe, Godswill; Dzama, Kennedy
ABSTRACT: Ninety-five farmers were involved in deriving a set of social, environmental, and economic sustainability indicators, which were used to assess sustainability of the smallholder cattle production system in Ncorha and Gxwalibomvu communities in the Eastern Cape, South Africa. The derived indicators were scored on a 5-point Likert-type scale and aggregated to provide a net sustainability score. Net sustainability scores were grouped into three categories; non-sustainable (<33%), partially sustainable (33–65%), and sustainable (>65%). Aggregate sustainability scores showed that the smallholder cattle production system in Ncorha and Gxwalibomvu, respectively, was socially (48.2% and 56.6%) and environmentally (54.2% and 57%) partially sustainable, but economically (15.7% and 10.8%) non-sustainable. Aggregate scores of the two communities (Ncorha, 37% and Gxwalibomvu, 41.0%) indicated that they were both partially sustainable. Holistic agroecological interventions and institutional support have the potential to improve the economic dimension of sustainability while simultaneously maintaining or improving the social and environmental dimensions. Adoption of agroecological interventions can be facilitated through farmer field schools.